Comparing students' responses to synchronous written corrective feedback during individual and collaborative writing tasks. Issue 1 (21st March 2022) - Cho, Hyejin; Kim, YouJin; Park, Seyoung
Abstract: The present study examined students' attention to linguistic forms during writing tasks and compared individual and collaborative writing conditions. Furthermore, the ways students in both conditions process indirect synchronous written corrective feedback (SWCF) and the ways they respond to it (i.e., uptake) were investigated. The target linguistic forms were Korean honorifics, which are closely related to Korean culture, honoring the elderly by using a different set of linguistic features. Twenty-nine learners of Korean were divided into two groups: collaborative and individual writing groups. The collaborative group completed e-mail writing tasks in pairs, whereas students in the individual group carried out the same tasks alone. During the tasks, indirect SWCF was provided on the target pragmatic features (i.e., honorifics). Think-aloud protocols and pair talk were audio-recorded. Students' attention to linguistic forms was operationalized as the occurrence of language-related episodes (LREs), and their processing of SWCF was determined using feedback-related episodes (FREs). Uptake was identified based on students' final writing output. The findings suggest that the collaborative group resolved linguistic errors more accurately than the individual group. In terms of the linguistic target features and uptake of SWCF, both groups demonstrated similar patterns, suggesting mediating effects of SWCF on students' task performance.